2015
DOI: 10.5937/fmet1504295s
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and managing operational risk in industrial processes

Abstract: The risk of not achieving process outcomes in key processes should be identified and reduced to achieve better results. The identification of risks involves defining the possible events that compromises the achievement of process outcomes and also the consequences of the occurrence of these events. This paper proposes a methodology to minimize operational/technical risk across different processes or departments, minimizing the possibility of spending excessive resources in a given process while other processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
8
0
3
Order By: Relevance
“…The equation of the intersecting plane for the spheres (1) and (2) can be obtained by taking difference of (1) and (2). This equation of intersecting plane is given in (5).…”
Section: Model's Input and Output Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…The equation of the intersecting plane for the spheres (1) and (2) can be obtained by taking difference of (1) and (2). This equation of intersecting plane is given in (5).…”
Section: Model's Input and Output Informationmentioning
confidence: 99%
“…Long-life operation and maintenance of technical objects requires special attention on the condition monitoring methods, strategies chosen in maintenance routine and evaluation of risks that should be performed to prioritize actions that reduce the global impact on the organization or system outcomes [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in [31], the authors defined the reliability of production process in the context of the probability of consumer demand and the performance level of a production system. The authors of [52] propose a very general definition, taking reliability of system/process as the likelihood of events that prejudice the achievement of results.…”
Section: Supportabilitymentioning
confidence: 99%
“…Moreover, a number of studies may be found in the literature covering the risk analysis of production processes/systems performance based on the use of basic reliability analysis methods (e.g. [4,25,52]), or diagnostics and forecasting for maintenance of production systems and processes (e.g. work [57]).…”
Section: Supportabilitymentioning
confidence: 99%
See 1 more Smart Citation